Phytoseiid mites (Acari: Mesostigmata: Phytoseiidae) associated with Cerrado biome plants in Brazil, with description of a new species - Demite, Peterson Rodrigo; Dias, Monique Andrade; Cavalcante, Ana Cristina Cerqueira; Ramos, Marcus Vinícius Vieitas; Lofego, Antonio Carlos [UNESP] (Systematic and Applied Acarology Society, 2017)
A survey of plants in 24 areas of the Cerrado biome in the states of Goiás and Minas Gerais (Brazil) revealed a total of 34 species of phytoseiid mites belonging to 16 genera and three subfamilies of the Phytoseiidae. A new species, Neoseiulus goiano n. sp., is described and illustrated. Morphological information is provided for the species collected in this study.
Keywords: Biological control agents; ecosystem services; hotspots; natural environments; predators